Prospective Evaluation of Positivity Rates of Aspergillus-Specific IgG and Quality of Life in HIV-Negative Tuberculosis Patients in Lagos, Nigeria - Oladele, Rita O.; Gbajabimiala, Titi; Irurhe, Nicholas; Skevington, Suzanne M.; Denning, David W. (Frontiers in Cellular and Infection Microbiology, 2022)
Background Pulmonary tuberculosis (PTB) often results in residual anatomical and functional changes despite microbiological cure and may be complicated by chronic pulmonary aspergillosis (CPA). In this study, we determined the perceived health-related quality of life (HRQoL) of patients during and after PTB therapy and compared it with their quantitative Aspergillus-specific IgG positivity rates. Methodology We conducted a longitudinal study among TB patients attending two directly observed therapy short-course (DOTS) clinics in Lagos, Nigeria. Two hundred and four confirmed TB patients were recruited over 9 months, with five visits at baseline and 3, 6, 9, and 12 months. They were all acid-fast bacilli smear, GeneXpert, or culture positive for Mycobacterium tuberculosis. Two HRQoL questionnaires translated into Yoruba were self-administered. Chest X-ray and Aspergillus IgG were collected at each visit. Results A total of 204 participants were recruited into this study. Most (70.6%) were age 18–39 years, and only 3.9% were above 60 years; 66.7% of all participants were males. A total of 189 (92.6%) participated in the 3-month assessment, 174 (85.3%) at 6 months, 139 (68.1%) at 9 months, and 99 (48.5%) at 12 months. At baseline, only 60.9% scored “good” or “very good” QoL and health on the WHOQOL-Bref, which improved to 77% at 6 months. At baseline, 10.4% had positive Aspergillus IgG levels, 15.1% at 3 months, 11.5% at 6 months, 16.7% at 9 months, and 19.3% at 12 months. Those with a positive Aspergillus IgG at 6 months had worse physical health (p = 0.001), psychological state (p = 0.002), social relationships (p = 0.006), and environmental QoL (p = 0.001) domains of the WHOQOL-Bref. Probable CPA was 10.4% at baseline and 19.3% at 6 months post-PTB therapy. Thirty-eight (18.6%) relocated after 6 months of treatment, 16 (7.8%) were lost to follow-up, and 11 (5.4%) died. Conclusion Our findings reveal a significant relationship between the QoL and Aspergillus IgG levels of TB patients. Further follow-up studies and additional imaging are required to determine when patients develop CPA and its clinical impact.